Bioderived ‘Self-N-doped reduced graphene oxide Nanoplatelets-like carbon’ from fruit waste ‘Carica papaya’ seeds and its electrochemical application - Rahul Kumar; Devkumari Patel; Manorama Singh (Discover Electrochemistry)
Abstract These days, carbon materials now play a major role in composite production. Graphene-like carbon materials stand out due to their unique properties: exceptional stability, biocompatibility, and a high surface-to-volume ratio. Graphene-like carbon sheets with doped heteroatoms show improved electrocatalytic activity, beneficial for various electrochemical uses, including sensors. etc. Waste materials offer a low-cost and environmentally safe approach to manufacturing such efficient materials. Herein, the low-temperature synthesis of self-N-doped reduced graphene oxide nanoplatelets-like-carbon material (N-rGONPsC) via condensation-bio-polymerization (C-B-P) mechanism was reported using fruit waste, i.e. ‘Carica papaya’ seeds as a source. The effect of time on the synthesis of bioderived carbon was also studied. One-step preparation was adopted without using any external N-doping agents. Characterisations were done with XRD, FT-IR, Raman, SEM with EDAX, TEM with SAED, TGA and XPS. We studied the specific surface area with BET surface analysis. Further, the electrochemical behaviour was studied with cyclic voltammograms for use in electrochemical sensing devices in future perspectives. The proposed study is an economical, eco-friendly, and sustainable way.